2010
DOI: 10.2478/s11686-010-0002-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in prevalence and cercarial development of Echinostephilla patellae (Digenea, Philophthalmidae) in the intertidal gastropod Patella vulgata

Abstract: The trematode Echinostephilla patellae is an abundant but scarcely investigated parasite found in coastal ecosystems of the British Isles. Redial and cercarial stages of the digenean occur in the digestive gland and gonads of common limpets Patella vulgata. Here, we present data on the temporal distribution of E. patellae infections in P. vulgata from an intertidal site on the Irish south coast as well as on the intramolluscan development of the cercariae over a period of one year. Prevalence of infection show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
10
0
3
Order By: Relevance
“…Curtis and Hurd 1983;Hechinger and Lafferty 2005;Koprivnikar et al 2007;Merlo and Etchegoin 2011). In addition, Prinz et al (2010) observed that the temperature increase coincides with a large number of definitive hosts and with a consequent increase in parasite prevalence in the mollusc hosts. The same pattern could apply to the community of larval digeneans in H. australis because during the warmer months (September to April), the Mar Chiquita lagoon becomes an important site for migratory birds as well as a breeding area for native species (Botto et al 1998;Ferrero 2001).…”
Section: Discussionmentioning
confidence: 85%
“…Curtis and Hurd 1983;Hechinger and Lafferty 2005;Koprivnikar et al 2007;Merlo and Etchegoin 2011). In addition, Prinz et al (2010) observed that the temperature increase coincides with a large number of definitive hosts and with a consequent increase in parasite prevalence in the mollusc hosts. The same pattern could apply to the community of larval digeneans in H. australis because during the warmer months (September to April), the Mar Chiquita lagoon becomes an important site for migratory birds as well as a breeding area for native species (Botto et al 1998;Ferrero 2001).…”
Section: Discussionmentioning
confidence: 85%
“…Infection in macaques by directly transmitted nematodes occurs in a cyclic yearly pattern based on breeding season (Macintosh et al 2010). The trematode, Echinostephilla patellae, infection peaks during the summer months because appropriate temperatures allow higher densities of the host, common limpets (Prinz et al 2010). This unimodal pattern can also be seen in Conopid flies parasitizing wild bumblebee species.…”
Section: Discussionmentioning
confidence: 98%
“…Depending on the parasite load, 5 to 25 sporocysts per snail were randomly selected and transferred to a glass slide to determine the developmental stages of their contents under the microscope. The number of developmental stages contained in daughter sporocysts was determined, ascribing them to the categories described in Prinz et al (2010) and Fermer et al (2010), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The co-occurrence of the three stages and the absence of sporocysts containing germinal balls exclusively indicates that M. obovata and C. labracis have a short prepatent infection, as demonstrated in e.g. Echinostephilla patellae (Prinz et al 2010) or Parvatrema minutum (as Meiogymnophallus minutus in Fermer et al 2009Fermer et al , 2010. This allows a continuous rapid production of mature cercariae and their emergence from the snail.…”
Section: Snail and Sporocyst Size In Relation To Parasite Datamentioning
confidence: 99%
See 1 more Smart Citation